Does the Addition of Pain Neurophysiology Education to a Therapeutic Exercise Program Improve Physical Function in Women with Fibromyalgia Syndrome? Secondary Analysis of a Randomized Controlled Trial - Ceballos-Laita, Luis (J Clin Med, 2021)
Therapeutic exercise (TE) is one of the most investigated approaches for the management of FMS. Pain neurophysiology education (PNE) helps toward understanding the pain condition, leading to maladaptive pain cognitions and coping strategies in patients with chronic pain. Our study aimed to assess the effects of therapeutic exercise and pain neurophysiology education versus TE in isolation on fatigue, sleep disturbances, and physical function in the short term and at three months of follow-up in women with fibromyalgia syndrome (FMS). A single-blind randomized controlled trial was carried out. A total of 32 women with FMS referred from medical doctors and fibromyalgia association were randomized in 2 groups: PNE + TE group or TE group. Fatigue and sleep disturbances (Visual Analog Score) and physical function (Senior Fitness Test) were assessed before, after intervention, and at three months of follow-up. Significant improvements were achieved in the Timed Up and Go test (p = 0.042) and Arm Curl test (p = 0.043) after intervention and on handgrip in the non-dominant side at three months of follow-up (p = 0.036) on the PNE + TE group. No between-groups differences were found for fatigue, sleep disturbances, and the rest of test included in the Senior Fitness Test. In conclusion, these results suggest that PNE + TE appears to be more effective than TE in isolation for the improvement of physical function (Timed Up and Go test and Arm Curl test) in women with FMS in the short term.